2013
DOI: 10.1017/jfm.2013.140
|View full text |Cite
|
Sign up to set email alerts
|

Lateral controls on grounding-line dynamics

Abstract: We present a theoretical and experimental study of viscous gravity currents introduced at the surface of a denser inviscid fluid layer of finite depth inside a vertical HeleShaw cell. Initially, the viscous fluid floats on the inviscid fluid, forming a self-similar, buoyancy-driven current resisted predominantly by the viscous stresses due to shear across the width of the cell. Once the viscous current contacts the base of the cell, the flow can be considered in two regions: a grounded region in which the curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
46
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 28 publications
(50 citation statements)
references
References 18 publications
4
46
0
Order By: Relevance
“…A further aspect of confinement relates to the contact between the injected current and the underlying boundary, which partitions the flow at a moving contact line between a region spanning the depth of the medium and a region containing the interface between the fluids. This moving contact line is analogous to that which arises in studies of shear-dominated viscous flows that are separated between a floating and a grounded component (Pegler et al 2013b).…”
mentioning
confidence: 64%
See 1 more Smart Citation
“…A further aspect of confinement relates to the contact between the injected current and the underlying boundary, which partitions the flow at a moving contact line between a region spanning the depth of the medium and a region containing the interface between the fluids. This moving contact line is analogous to that which arises in studies of shear-dominated viscous flows that are separated between a floating and a grounded component (Pegler et al 2013b).…”
mentioning
confidence: 64%
“…Instead, the closure of the integration of (2.14) for h is maintained by the imposition of (2.8a,b), which govern the evolution of the newly formed contact line (cf. Pegler et al 2013b). Condition (3.1) presupposes that the flow is introduced horizontally at the source.…”
Section: Injection At a Line Sourcementioning
confidence: 99%
“…By making the minor alteration of replacing the reduced gravity ∆ρg/ρ 0 with the reduced gravity relevant to a floating fluid layer ∆ρg/ρ a (e.g. Pegler et al 2013b), the relevant value of U is found to be Figure 15. Comparison between the experimental thickness profile H(x, t) (solid curves) and the theoretical prediction (dashed curve), plotted in terms of the similarity variables defined by (3.3) and (3.4).…”
Section: Experimental Studymentioning
confidence: 99%
“…However, at this juncture the argument used in appendix A cannot be continued to develop an equation forẋ U because the flux towards the upper contact line q(x U , t) does not vanish in accord with (2.18). The same difficulty arises in modelling the contact line that separates a floating and grounded component of a gravity current in a Hele-Shaw cell (Pegler et al 2013).…”
mentioning
confidence: 99%
“…To evaluate the right-hand side of (2.20) numerically, we utilize the same method of Pegler et al (2013), whereby ∂h/∂t is calculated using the result of a trial integration step under an artificial imposition ofẋ U = 0. The predicted penetration of the current through the top boundary δh = h − H arising from this trial is then used to evaluate the rate of propagation (2.20) asẋ…”
mentioning
confidence: 99%